2011
DOI: 10.1159/000334880
|View full text |Cite
|
Sign up to set email alerts
|

Have We Enough Glutamine and How Does It Work? A Clinician’s View

Abstract: There is a gap between the scientific basis of the claim that in several disease states glutamine is lacking and the widespread belief that supplementation of glutamine to the nutritional regimen is beneficial in severely ill patients. Glutamine shortage exists when consuming tissues, playing a crucial role in the response to trauma and disease, receive insufficient amounts of glutamine. In these tissues (immune system, wound), glutamine is only partly oxidized but has more specific roles as nontoxic nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 82 publications
1
28
0
2
Order By: Relevance
“…In colonic cancer patients undergoing surgery, plasma glutamine levels drop by 30 %, independently of the previous glutamine depletion [296]. In severe pancreatitis [297] and trauma patients [298], plasma glutamine levels decrease to less than 50 % of its basal levels as compared to control values. Similar effects have also been seen in experimental animal models of sepsis, followed by severe adaptive immune system suppression (low T and B lymphocyte responses) [50,209,299].…”
Section: Physical Exercise Glutamine and Hs Response In Agingmentioning
confidence: 98%
“…In colonic cancer patients undergoing surgery, plasma glutamine levels drop by 30 %, independently of the previous glutamine depletion [296]. In severe pancreatitis [297] and trauma patients [298], plasma glutamine levels decrease to less than 50 % of its basal levels as compared to control values. Similar effects have also been seen in experimental animal models of sepsis, followed by severe adaptive immune system suppression (low T and B lymphocyte responses) [50,209,299].…”
Section: Physical Exercise Glutamine and Hs Response In Agingmentioning
confidence: 98%
“…In these cells of rapid turnover, nitrogen may be used in the production of needed amino acids, and purines and pyrimidines for DNA and RNA synthesis. 81 Its metabolic functions include provision of NADPH and increasing insulin sensitivity. 81 Glutamine also appears to have a role in leukocyte apoptosis, superoxide production, antigen processing, and phagocytosis.…”
Section: Arginine and Glutamine In Wound Healingmentioning
confidence: 99%
“…81 Its metabolic functions include provision of NADPH and increasing insulin sensitivity. 81 Glutamine also appears to have a role in leukocyte apoptosis, superoxide production, antigen processing, and phagocytosis. 82,83 The suggested anti-inflammatory and immune activity may include activation of Figure 8.…”
Section: Arginine and Glutamine In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors of the "generalized" hypoaminoacidemia in the development of a patient's critical condition are the increased AA distribution due to vasodilation and increased permeability of the endothelium, an inhibition of the synthesis of a number of AAs in the liver and their increased consumption in central tissues (immune system, liver, spleen, wound). [46,87] Experimental data have shown that stress factors increased the KYNA formation and other metabolites of KP of tryptophan catabolism by activating the secretion of glucocorticoids and a significant increase in the activity of TDO [88] and IDO, which is regulated by cytokines. [89] The increased KYNA concentration after acute physiological stress was observed in clinical studies performed by E. KotlinskaHasiec et al…”
Section: Rgn and Sepsismentioning
confidence: 99%